Una nota a la tésera “Turiel 4” (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
In this paper the transcription and reading of the tessera hospitalis “Turiel 4” are presented, considering the metalographic study made by Dr. Salvador Rovira Lloréns. According to him, approximately half of the inscription would be recent.